Tindakan Sosial Perajin Gerabah dalam Ketahan Industri Gerabah di Desa Bentangan Kecamatan Wonosari Kabupaten Klaten - Nurahadatul 'Aisy Qodtrunada (Journal of Development and Social Change, 2025)
The pottery industry in Bentangan Village is one of the industries that has managed to survive amidst economic changes. However, its sustainability is at risk due to the declining number of artisans and the lack of regeneration. This study aims to analyze the resilience of artisans in facing challenges and examine the social actions underlying their choices. The research employs a qualitative descriptive approach, with data collected through interviews, observation, and documentation. The findings are analyzed using Max Weber's social action theory and resilience theory. The results indicate that the social action of pottery artisans can be categorized into Weber's four types of actions: affectual, traditional, instrumental-rational, and value-rational actions. Most artisans continue their work primarily due to economic factors, without considering long-term business development. Their resilience in overcoming challenges is largely individual, with little to no support from community systems or sustainable policies.